The future of world and Czech mechanical watch business - Reischl, Václav; Bolotov, Ilya; Král, Petr, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The mechanical watch business has been around for many centuries. Nevertheless with the rise of technology one could expect that the industry would decline. Therefore this thesis focuses on the current development of the global and Czech watch industries with some implications for the future. It firstly analyzes the international flows of mechanical watches and then introduces the main global mechanical watch producers. Secondly it examines the history and current state of the Czech watch industry and presents a practical example of a company called Prostě Prim that focuses on resale of vintage Czechoslovak watches Prim.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses